Back Cover: Unidirectional Presentation of Membrane Proteins in Nanoparticle‐Supported Liposomes (Angew. Chem. Int. Ed. 29/2019). Issue 29 (25th June 2019) - Chen, Wen; Cai, Yongfei; Fu, Qingshan; Chen, Bing; Guo, Junling; Chou, James J.
Abstract : Presentation of membrane proteins to host immune systems in a conformation‐specific manner is a major challenge in vaccine or antibody development. In their Communication on page 9866 ff., J. Guo, J. J. Chou, et al. developed a method to address this challenge. They used a functionalized nanoparticle as a substrate to guide the formation of proteoliposome that can unidirectionally present many copies of membrane proteins.